Sphingolipids as critical players in retinal physiology and pathology - Simon, Maria Victoria (2021)
Sphingolipids have emerged as bioactive lipids involved in the regulation of many physiological and pathological processes. In the retina, they have been established toparticipate in numerousprocesses, suchas neuronal survival and death, proliferation and migration of neuronal and vascular cells, inflammation, and neovascularization. Dysregulation of sphingolipids is therefore crucial in the onset and progression of retinal diseases. This review examines the involvement of sphingolipids in retinal physiology and diseases. Ceramide (Cer) has emerged as a common mediator of inflammation and death of neuronal and retinal pigment epithelium cells in animal models of retinopathies such as glaucoma, age-related macular degeneration (AMD), and retinitis pigmentosa. Sphingosine- 1-phosphate (S1P) has opposite roles, preventing photoreceptor and ganglion cell degeneration but also promoting inflammation, fibrosis, and neovascularization in AMD, glaucoma, and pro-fibrotic disorders. Alterations in Cer, S1P, and ceramide 1- phosphate may also contribute to uveitis. Notably, use of inhibitors that either prevent Cer increase or modulate S1P signaling, such as Myriocin, desipramine, and Fingolimod (FTY720), preserves neuronal viability and retinal function. These findings underscore the relevance of alterations in the sphingolipid metabolic network in the etiology of multiple retinopathies and highlight the potential of modulating their metabolism for the design of novel therapeutic approaches.